MENGUJI EFEK MERGER TERHADAP KINERJA SAHAM PT BANK SYARIAH INDONESIA TBK - Rakhmat Hadi Sucipto (Journal of Management Small and Medium Enterprises (SMEs), 2023)
The objective of this research was to examine the impact of the merger of three national Islamic banks, specifically PT Bank Syariah Mandiri Tbk, PT Bank BRI Syariah Tbk, and PT Bank BNI Syariah on the Indonesia Stock Exchange's stock trading variables such as price, frequency, volume, and value. The research employed a quantitative approach, and a simple sample t-test was used for analysis. The analysis revealed a notable difference in the company's stock price before and after the merger. However, the findings of other tests indicate no significant difference in the frequency of stock trading, share volume, and stock trading value between the pre and post-merger phases of the companies. Keywords: Merger; Stock; Bank